Driving cryptosystems with hyperchaotic signals: an approach involving linear observers - G. Grassi; S. Mascolo (2000 IEEE International Symposium on Circuits and Systems (ISCAS), 2000)
In this paper a method for designing cryptosystems driven by hyperchaotic signals is developed. The idea is to transmit a proper hyperchaotic signal, so that the receiver behaves as a linear observer for the state of the transmitter. The proposed tool proves to be: (i) rigorous, since some propositions are given for obtaining the plaintext at the receiver in a rigorous way; (ii) flexible, since a wide class of cryptosystems is designed by exploiting different hyperchaotic transmitting circuits; (iii) efficient, since the hyperchaotic carrier masks the encrypted signal, which in turn hides the message signal. The combination of hyperchaos, cryptography and complex transmitted signal makes a contribution to the development of communication systems with higher security.
Keywords: Cryptography; Transmitters; Signal design; Communication system security; Chaotic communication; Equations; Chaos; Design methodology; Flexible printed circuits; Communication systems